2014
DOI: 10.1016/j.tcb.2013.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Guest list or black list: heritable small RNAs as immunogenic memories

Abstract: Small RNA-mediated gene silencing plays a pivotal role in genome immunity by recognizing and eliminating viruses and transposons which otherwise may colonize the genome. However, this can be challenging since individual genomic parasites are highly diverse, and employ multiple immune evasion techniques. In this review, I discuss a new theory proposing that the integrity of the germline is maintained by transgenerationally-transmitted RNA "memories" that record ancestral gene expression patterns, and delineate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 88 publications
0
34
0
2
Order By: Relevance
“…As discussed 572 above, that is a kind of modification that can result from a treatment with exo-dsRNAs 573 without reliance on continued transcription (Rechavi, 2014 Likewise, EPA could have reduced compliance costs for those using exo-dsRNA in contained 596 facilities by limiting the approval to synthetically produced dsRNA molecules, as requested 597 in the original application, prohibiting dsRNA derived from pathogens such as RNA viruses. 598…”
Section: Conclusion 500 501mentioning
confidence: 99%
“…As discussed 572 above, that is a kind of modification that can result from a treatment with exo-dsRNAs 573 without reliance on continued transcription (Rechavi, 2014 Likewise, EPA could have reduced compliance costs for those using exo-dsRNA in contained 596 facilities by limiting the approval to synthetically produced dsRNA molecules, as requested 597 in the original application, prohibiting dsRNA derived from pathogens such as RNA viruses. 598…”
Section: Conclusion 500 501mentioning
confidence: 99%
“…Quelles sont les fenêtres de sensibilité, d'insensibilité à ces facteurs ? Comment les différences liées au sexe des parents imposent-elles un dimorphisme sexuel sur la progéniture voire les générations suivantes [3,12,26,29,56] ? L'implication de l'épigénétique dans les effets/réponses inter/transgénérationnels manque encore d'un modèle fédérateur [29].…”
Section: Références Perspectivesunclassified
“…In the plant Arabidopsis, epigenetic inheritance can occur over at least eight generations (Johannes et al, 2009;Cortijo et al, 2014). In the nematode worm Caenorhabditis elegans, stable transmission across generations depends on gene regulation by microRNA (Rechavi, 2014). Rassoulzadegan (2011) found that injection of RNA from sperm from one strain of mice into wild-type embryos led to a distinct phenotype in the offspring, which was in turn transmitted to their progeny.…”
Section: Epigeneticsmentioning
confidence: 99%